Surface modification for improving the formability of SPA laminated composite - (:unkn) unknown (ELSEVIER SCI LTD, 1999)
The effect of surface modification on the formability of Steel-Polymer-Aluminium (SPA) laminated composites was investigated. Different types of adhesives were used as polymer layer. The layer thickness varied from 0.1 to 0.4 mm. Various surface modification models were designed. The combinations of surface models, adhesive types and layer thickness effects were investigated by both the experimental and numerical methods. The experimental results showed that the formability of SPA laminated composite is improved by surface modification. In addition to this, the effects of layer thickness and adhesive types were also observed. Experimental results were used to construct a numerical model to study the effect of these variables. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: Steel-Polymer-Aluminium laminated composite; adhesives; Steel-Polymer-Steel laminates; STEEL LAMINATE